Pre- and post-GFC policy multipliers - Ouliaris, Sam,Rochon, Céline (International Monetary Fund, 2020)
This paper estimates the change in policy multipliers in the U.S. relative to their pre-2008 financial crisis levels using an augmented Blanchard-Perotti model to allow for the dynamic effects of shocks to the central bank balance sheet, real interest rates and debt levels on economic activity. Given the elevated debt level and significantly larger central bank balance sheet in the U.S. after 2008, the paper estimates the likely impact of new stimulus packages. We find that expenditure multipliers have fallen post-2008 crisis because of higher government debt, implying that the effectiveness of fiscal policy has declined. The analysis also investigates the impact of quantitative easing. The results suggest that it is beneficial, but requires sizable balance sheet interventions to lead to noticeable effects on real GDP. The results are used to assess the impact of the policy packages to address COVID-19. Because of rising debt stocks, dealing with a crisis is becoming more and more costly despite the current low interest rate environment
10.5089/9781513561097.001
Keywords: Graue Literatur; Business and Economics; Macroeconomics; Economics: General; International Economics; Macroeconomic Policy; Macroeconomic Aspects of Public Finance; and General Outlook: General; Fiscal Policy; Comparative or Joint Analysis of Fiscal and Monetary Policy; Stabilization; Treasury Policy; Model Construction and Estimation; Economic & financial crises & disasters; Economics of specific sectors; Financial crises; Economic sectors; Currency crises; Informal sector; Economics; fiscal multipliers; structural VAR; financial crisis (GFC)